Sensor Technology Performance under Environmental Interference: A Comparative Evaluation Model - Semiu Temidayo Fasasi,; Oluwapelumi Joseph Adebowale,; Zamathula Queen Sikhakhane Nwokediegwu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Sensor technologies are increasingly integral to a wide range of industrial, environmental, and infrastructural applications. However, their performance is often compromised by environmental interference such as temperature fluctuations, humidity, particulates, and electromagnetic noise. Traditional evaluation methods, focused primarily on laboratory-based metrics, fail to account for the real-world variability these technologies encounter in the field. This paper presents a comparative evaluation model designed to assess sensor performance under such interference systematically. The model introduces a structured framework based on four key dimensions, robustness, response fidelity, degradation rate, and adaptability, which together offer a comprehensive view of sensor resilience. A tailored set of performance metrics, including accuracy loss under thermal variation and detection delays in high humidity, provides measurable criteria for assessing sensor suitability. To accommodate application-specific priorities, the model incorporates a weighted comparative mechanism using multi-criteria decision analysis principles. Sensor types are categorized by operational principle and mode, then evaluated across environmental challenges using a conceptual performance matrix. The analysis reveals trade-offs between sensitivity, robustness, cost, and response time across sensor classes. By bridging the gap between laboratory performance and field reliability, the proposed model offers valuable guidance for sensor selection, design improvement, and future benchmarking efforts.
Keywords: Sensor performance evaluation; Environmental interference; Robustness metrics; Comparative analysis; Sensor classification